Changes in leaf physiology caused by Calacarus heveae (Acari, Eriophyidae) on rubber tree - Daud, Rodrigo Damasco; Conforto, Elenice de Cassia [UNESP]; Fazzio Feres, Reinaldo Jose [UNESP] (Springer, 2012)
The influence of Feres on physiological processes was evaluated in two rubber tree clones. Experiments were conducted in a greenhouse with 5-month-old potted seedlings of RRIM 600 and GT 1 clones, that were either infested with or not (non-infested control). The level of photosynthetic pigments, net photosynthetic rate, stomatal conductance, transpiration rate, changes in relative humidity between leaf surface and ambient air (Delta w) and intercellular CO2 concentration (Ci CO2) were evaluated. Infested plants showed significant reductions in the rate of transpiration, the rate of photosynthesis, stomatal conductance and Delta w. RRIM 600 seedlings showed more pronounced physiological damage than GT 1 seedlings, indicating a lower physiological tolerance of the former clone to the mite. However, carotenoid levels were reduced only in GT 1 seedlings. Photosynthesis was probably reduced due to a decrease in stomatal opening, as indicated by reductions in transpiration rate and stomatal conductance and by the absence of differences in chlorophyll levels between treatments. Our results indicate that populations of reduce the productivity of rubber trees. Thus, farmers must to be aware to control this mite pest in rubber tree plantations.
Keywords: Arthropods and plants; Clones; Herbivory; Hevea brasiliensis; Photosynthesis; Phytophagous mites